Downregulation of nitrovasodilator-induced cyclic GMP accumulation in cells exposed to endotoxin or interleukin-1 beta. - Papapetropoulos, A. (1996)
1. Induction of nitric oxide synthase (iNOS) results in overproduction of nitric oxide (NO), which may be a principal cause of the massive vasodilatation and hypotension observed in septic shock. Since NO-induced vasorelaxation is mediated via the soluble isoform of guanylate cyclase (sGC), the regulation of sGC activity during shock is of obvious importance, but yet poorly understood. The aim of the present study was to investigate the activation of sGC by sodium nitroprusside (SNP) before and after exposure of rat aortic smooth muscle cells to endotoxin (LPS) or interleukin-1 beta (IL-1 beta). 2. Exposure of rat aortic smooth muscle cells to SNP (10 microM) elicited up to 200 fold increases in cyclic GMP. This effect was attenuated by 30-70% in IL-1 beta- or LPS-pretreated cells, in a pretreatment time-and IL-1 beta- or LPS-concentration-dependent manner. When, however, cells were exposed to IL-1 beta or LPS and then stimulated with the particulate guanylate cyclase activator, atriopeptin II, no reduction in cyclic GMP accumulation was observed. 3. Pretreatment of rats with LPS (5 mg kg-1, i.v.) for 6 h led to a decrease in aortic ring SNP-induced cyclic GMP accumulation. 4. The IL-1 beta-induced reduction in SNP-stimulated cyclic GMP accumulation in cultured cells was dependent on NO production, as arginine depletion abolished the downregulation of cyclic GMP accumulation in response to SNP. 5. Reverse-transcriptase-polymerase chain reaction analysis revealed that the ratio of steady state mRNA for the alpha, subunit of sGC to glyceraldehyde phosphate dehydrogenase was decreased in LPS- or IL-1 beta-treated cells, as compared to vehicle-treated cells. 6. Protein levels of the alpha 1 sGC subunit remained unaltered upon exposure to LPS or IL-1 beta, suggesting that the early decreased cyclic GMP accumulation in IL-1 beta- or LPS-pretreated cells was probably due to reduced sGC activation. Thus, the observed decreased responsiveness of sGC to NO stimulation following cytokine or LPS challenge may represent an important homeostatic mechanism to offset the extensive vasodilatation seen in sepsis.